2015
DOI: 10.1039/c5nr04809e
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis-induced elasticity modulation in a superionic proton conductor probed by band-excitation atomic force microscopy

Abstract: Variable temperature band-excitation atomic force microscopy in conjunction with I-V spectroscopy was used to investigate the crystalline superionic proton conductor CsHSO4 during proton exchange induced by a Pt-coated conductive scanning probe. At a sample temperature of 150 °C and under an applied bias <1 V, reduction currents of up to 1 nA were observed. Simultaneously, we show that the electrochemical reactions are accompanied by a reversible decrease in the elastic modulus of CsHSO4, as seen by a contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This modulation voltage vibrates the tip into the sample (or sample into tip), and the amplitude and phase of the resulting lever oscillations are decoupled, in a similar way to PFM. Combining CR-AFM with voltage spectroscopy has shown it is possible to explore local bias-induced phenomena ranging from purely bias induced elastic softening to surface electrochemical processes [91,112].…”
Section: Contrast In Vm-afmmentioning
confidence: 99%
“…This modulation voltage vibrates the tip into the sample (or sample into tip), and the amplitude and phase of the resulting lever oscillations are decoupled, in a similar way to PFM. Combining CR-AFM with voltage spectroscopy has shown it is possible to explore local bias-induced phenomena ranging from purely bias induced elastic softening to surface electrochemical processes [91,112].…”
Section: Contrast In Vm-afmmentioning
confidence: 99%
“…In parallel, acoustic detection , of phase transitions and electrochemical reactions with SPM has been recently demonstrated, where the changes in contact resonant frequency are monitored as a function of some stimulus. For instance, Papandrew et al directly observed changes in the elastic modulus of a proton conductor at high temperature after application of bias when in the superionic phase. Similarly, Li et al have observed elastic softening before an onset of a structural phase transition in BiFeO 3 thin films, which has also been explored by other groups .…”
Section: Morphology and Single-point Current–voltage Investigation Of...mentioning
confidence: 99%
“…However, emergence of amplitude based feedback and multiple frequency methods such as band excitation 188,190 has allowed to separate the electromechanical signal and resonant frequency both in imaging and spectroscopic PFM, as originally demonstrated by Maksymovych. 355 In the case of electrochemical reactions, Papandrew et al 356 noted the strong change in resonant frequency during bias application in CsHSO4 (CHS), coincident with reduction currents. CHS is a proton conductor at high temperature (above 140°C), but the changes in elastic modulus with voltage were absent in the room-temperature phase, or when non-catalytic probes were utilized, suggesting acoustic detection can be used as an effective probe of electrochemical reactions.…”
Section: D Acoustic Detectionmentioning
confidence: 99%